Identifying the unidentified fauna enhances insights into hominin subsistence strategies during the Middle to Upper Palaeolithic transition - Virginie Sinet-Mathiot; William Rendu; Teresa E. Steele; Rosen Spasov; Stéphane Madelaine; Sylvain Renou; Marie-Cécile Soulier; Naomi L. Martisius; Vera Aldeias; Elena Endarova; Paul Goldberg; Shannon J. P. McPherron; et al. (Archaeological and Anthropological Sciences, 2023)
Understanding Palaeolithic hominin subsistence strategies requires the comprehensive taxonomic identification of faunal remains. The high fragmentation of Late Pleistocene faunal assemblages often prevents proper taxonomic identification based on bone morphology. It has been assumed that the morphologically unidentifiable component of the faunal assemblage would reflect the taxonomic abundances of the morphologically identified portion. In this study, we analyse three faunal datasets covering the Middle to Upper Palaeolithic transition (MUPT) at Bacho Kiro Cave (Bulgaria) and Les Cottés and La Ferrassie (France) with the application of collagen type I peptide mass fingerprinting (ZooMS). Our results emphasise that the fragmented component of Palaeolithic bone assemblages can differ significantly from the morphologically identifiable component. We obtain contrasting identification rates between taxa resulting in an overrepresentation of morphologically identified reindeer ( Rangifer tarandus ) and an underrepresentation of aurochs/bison ( Bos/Bison) and horse/European ass ( Equus ) at Les Cottés and La Ferrassie. Together with an increase in the relative diversity of the faunal composition, these results have implications for the interpretation of subsistence strategies during a period of possible interaction between Neanderthals and Homo sapiens in Europe. Furthermore, shifts in faunal community composition and in carnivore activity suggest a change in the interaction between humans and carnivores across the MUPT and indicate a possible difference in site use between Neanderthals and Homo sapiens . The combined use of traditional and biomolecular methods allows (zoo)archaeologists to tackle some of the methodological limits commonly faced during the morphological assessment of Palaeolithic bone assemblages.

Neanderthal subsistence, taphonomy and chronology at Salzgitter‐Lebenstedt (Germany): a multifaceted analysis of morphologically unidentifiable bone - Karen Ruebens; Geoff M. Smith; Helen Fewlass; Virginie Sinet‐Mathiot; Jean‐Jacques Hublin; Frido Welker (Journal of Quaternary Science, 2023)
Pleistocene faunal assemblages are often highly fragmented, hindering taxonomic identifications and interpretive potentials. In this paper, we apply four different methodologies to morphologically unidentifiable bone fragments from the Neanderthal open‐air site of Salzgitter‐Lebenstedt (Germany). First, we recorded zooarchaeological attributes for all 1362 unidentifiable bones recovered in 1977. Second, we applied zooarchaeology by mass spectrometry (ZooMS) to 761 fragments, and calculated glutamine deamidation values. Third, we assessed the collagen preservation of 30 fragments by near‐infrared spectroscopy (NIR) and, finally, we pretreated 10 bones with high predicted collagen values for radiocarbon dating. All returned dates at, or beyond, the limit of radiocarbon dating, indicating an age of older than 51 000 years ago. The ZooMS faunal spectrum confirms a cold environment, dominated by reindeer, alongside mammoth, horse and bison. The low occurrence of carnivore modifications (1%) contrasts with an abundance of human modifications (23%). Cut marks and marrow fractures were observed across reindeer, horse and bison. The mammoth remains are less well preserved and show a lower degree of human modifications, indicating, perhaps, a different taphonomic history. Overall, this study illustrates the importance of retaining, studying and incorporating the unidentifiable bone fraction to optimize interpretations of site formation and subsistence behaviour at Palaeolithic sites.

Combining collagen extraction with mineral Zn isotope analyses from a single sample for robust palaeoecological investigations - Jeremy McCormack; Nicolas Bourgon; Virginie Sinet-Mathiot; Zeljko Rezek; Geoff M. Smith; Jean-Jacques Hublin; Mohammed Dabain; Helen Fewlass (Archaeological and Anthropological Sciences, 2022)
Collagen extraction from bones or dentine, commonly used for radiocarbon ( 14 C) dating and stable carbon and nitrogen isotope (δ 13 C and δ 15 N) analyses, involves the dissolution of the bioapatite of skeletal elements. This fraction is typically disposed of during pretreatment. Here, we test the possibility of utilising this dissolved mineral solution for analysis of the bioapatite zinc isotope composition (δ 66 Zn). Bioapatite δ 66 Zn is a novel trophic level indicator similar to collagen δ 15 N but with isotopic fractionation independent from nitrogen, thus providing additional dietary information. We tested ways to minimise Zn contamination of the dissolved mineral phase during collagen extraction. We then used archaeological bone samples from Ain Difla (Jordan) and Ranis (Germany) to compare δ 66 Zn values of dissolved bioapatite following our collagen extraction protocol with δ 66 Zn values from the same sample material dissolved in a metal-free cleanroom. Our results demonstrate that with only minor adjustments to minimise Zn contamination, the dissolved mineral solution from collagen extraction protocols commonly employed for 14 C dating and (palaeo)dietary analysis can be used for additional δ 66 Zn analyses even when collagen extraction does not take place in a cleanroom. Our protocol allows us to gain an additional dietary proxy to complement δ 15 N trophic level interpretations and perform more robust (palaeo)ecological investigations without further destructive sampling.